Tunable meta-liquid-crystal based on mercury microdrople - Chia, Elbert E. M. (2015)
Here we report a tunable Meta-Liquid-Crystal based on liquid metal droplet, the optical properties of which is tuned by controlled electrowetting effects. The Meta-LiquidCrystal consists of 80 × 80 micro droplets, which are formed and self-assembled by lotus effect on silicon substrate with micro holes array. In experiment, it measures a 0.01-THz frequency shift of the dipole resonance spectrum induced by changing of the droplets shape via electrowetting effect. The Meta-Liquid-Crystal is flexible in tuning and easy in fabrication, which has potential application on tunable filters, controllable beam steering and flat lens.